The Effect of Current Ratio (CR) and Assets Structure on Debt To Equity Ratio (DER) in PT Aneka Tambang Tbk from 2011 to 2020 - Akhmad Akbar; Endang Nurita (Indonesian Financial Review, 2022)
This study aims to determine the effect of the current ratio (CR) on the debt to equity ratio (DER) and the effect of asset structure on the debt to equity ratio (DER) partially and the effect of the current ratio (CR) and asset structure on the debt to equity ratio (DER). ) simultaneously at PT Aneka Tambang Tbk for the 2011-2020 period. The research method used in this study is descriptive quantitative. The population of this study is the annual financial statements of PT Aneka Tambang Tbk for the period 2011-2020 and the sample in this study is the financial position statements of PT Aneka Tambang Tbk for the period 2011-2020. Data analysis used hypothesis testing with t and F statistical tests using SPSS (Statistical Product and Service Solutions) 25. Partial research results show that the current ratio (CR) has no effect on debt to equity ratio (DER). Asset structure has no effect on the debt to equity ratio (DER). The results of the study simultaneously stated that the current ratio (CR) and asset structure had no effect on the debt to equity ratio (DER).